A Multicentre Italian Study on the Psychological Impact of an Inconclusive Cystic Fibrosis Diagnosis after Positive Neonatal Screening - Antonella Tosco; Diletta Marino; Sara Polizzi; Valentina Tradati; Rita Padoan; Claudia Giust; Benedetta Fabrizzi; Giovanni Taccetti; Lucia Merli; Vito Terlizzi (MDPI AG, 2023)
Background: An inconclusive diagnosis of cystic fibrosis (CF) after positive newborn screening (NBS) may cause parental distress. We compared the psychological impact of CF transmembrane conductance regulator-related metabolic syndrome (CRMS)/CF screen-positive, inconclusive diagnosis (CFSPID), and clear CF diagnosis, on parents. Methods: The participants were administered the Generalized Anxiety Disorder Scale, Patient Health Questionnaire-9, and the Italian version of the Impact of Event Scale-Revised as quantitative tools and semi-structured interviews as qualitative tools. Parental experience, child representation, relationships, future information, and perception of health status were investigated. Interviews were recorded and transcribed verbatim maintaining anonymity. Results: Thirty-two families were enrolled: sixteen with CF and CRMS/CFSPID, respectively. Anxiety and depression values were high in both groups, as were the measurement of traumatic impact subscales: avoidance, intrusiveness, and hyperarousal. The children's health was evaluated by respective parents as being nearly healthy. Conclusions: Our results highlight negative psychological impacts, including emotional and affective representations, on parents of children with inconclusive CF diagnosis compared with those with clear diagnosis.